Effects of Silymarin against Hepatic and Renal Toxicity Induced by Methotrexate in Rats. - Abdullah Ahmed, Watban; Qatea, Fouad Kadhim; Qasim, Ban Jumaah; Nashtar, Saad Badai; Al-Radeef, Mohanad Yasir (Tikrit Journal of Pharmaceutical Sciences, 2023)
Objective: The current study aimed to evaluate silymarin's prophylactic and therapeutic effects on methotrexate-induced nephron-hepatotoxicity in albino rats. Methods: Twenty-four rats were housed for 15 days in the animal unit facility at the College of Veterinary Medicine / Tikrit University and separated into six groups: 1st group was a healthy control group, the 2nd was a methotrexate induction group, the 3rd was considered therapeutic groups and received methotrexate single dose for one week then received silymarin at day 8 for one week, the 4th group was prophylactic group and received silymarin for one week then received methotrexate single dose for one week. Results: The nephrotoxicity and hepatotoxicity effects of methotrexate were reported via increasing levels of urea, creatinine, Alanine aminotransferase, aspartate aminotransferase, Alkaline Phosphatase, and decreasing Albumin in comparison to the control group. Therapeutic groups and the prophylactic group achieved a significant decrease in urea and creatinine, Alanine aminotransferase, aspartate aminotransferase, and Alkaline Phosphatase, while there was a significant increase in Albumin in the therapeutic and prophylactic group. Conclusion: It was concluded that silymarin had a therapeutic and a prophylactic effect against the nephrotoxicity and hepatotoxicity induced by methotrexate in albino rats. Keywords: Methotrexate, Nephrotoxicity, Hepatotoxicity, Silymarin